MORFOLOGI PERUMAHAN TERENCANA DI PINGGIRAN KOTA BANJARMASIN - Mutia, Indah (Politeknik Negeri Banjarmasin, 2011)
This paper is aimed at investigatingÂ the urban sprawl patterns caused by the develop-ment of planned housing (real estate/KPR) in Banjarmasin peri-urban areas (macro scale) and specifically analyzing the morphological characteristics (urban structure, build-ing and spatial layout) of that housing type in North Banjarmasin and Handil Bakti (micro scale). Findings show that the development of those planned housing has shaped a sporadic pattern or what so-called a leap frog development, in which they are concen-trated in North and South of Banjarmasin fringe-urban areas where availability of agricul-tural land is still abundant. Form three areas, the cluster of residential has a similarity in building and spatial layouts such as streets with grid system and rectangular plot and marked by a single entrance with enclosed cluster and no boundary between buildings / land plot.